2023
DOI: 10.1021/acsnano.3c03505
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Future Prospects for Memristive Materials, Devices, and Systems

Abstract: Memristive technology has been rapidly emerging as a potential alternative to traditional CMOS technology, which is facing fundamental limitations in its development. Since oxide-based resistive switches were demonstrated as memristors in 2008, memristive devices have garnered significant attention due to their biomimetic memory properties, which promise to significantly improve power consumption in computing applications. Here, we provide a comprehensive overview of recent advances in memristive technology, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 417 publications
(845 reference statements)
0
28
0
Order By: Relevance
“…[19,146] The artificial optoelectronic synapse could be realized in twoterminal memristors and three-terminal transistors. [93,147,148] He et al reported a W/n-MoS 2 /p-Si, demonstrating diverse synaptic neuromorphic functions, such as potentiation/habituation, long-term/short-term memory and paired-pulse facilitation. [149] In three-terminal devices, charge-trap transistors, floating-gate transistors and ferroelectric transistors are three type structure of optoelectronic synapse.…”
Section: Optoelectronic Synapsementioning
confidence: 99%
“…[19,146] The artificial optoelectronic synapse could be realized in twoterminal memristors and three-terminal transistors. [93,147,148] He et al reported a W/n-MoS 2 /p-Si, demonstrating diverse synaptic neuromorphic functions, such as potentiation/habituation, long-term/short-term memory and paired-pulse facilitation. [149] In three-terminal devices, charge-trap transistors, floating-gate transistors and ferroelectric transistors are three type structure of optoelectronic synapse.…”
Section: Optoelectronic Synapsementioning
confidence: 99%
“…The reason lies in the stochastic nature of the RS in the materials used in memristors . Thus, finding optimal materials to fabricate analog memristors suitable for use in NCSs is a critical development area in neuromorphic computing …”
Section: Introductionmentioning
confidence: 99%
“…Researchers are also exploring new memristive or quasi-memristive structures influenced by external stimuli other than electrical ones, such as magnetic fields, light, or temperature . However, the “classical” sandwich memristors, driven by an electric field, remain pivotal in the discipline and are widely viewed as one of the most promising for microelectronics …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations